2019
DOI: 10.1142/s0218348x1940005x
|View full text |Cite
|
Sign up to set email alerts
|

Overall PSD and Fractal Characteristics of Tight Oil Reservoirs: A Case Study of Lucaogou Formation in Junggar Basin, China

Abstract: Lucaogou tight oil reservoir, located in the Junggar Basin, Northwest of China, is one of the typical tight oil reservoirs. Complex lithology leads to a wide pore size distribution (PSD), ranging from several nanometers to hundreds of micrometers. To better understand PSD and fractal features of Lucaogou tight oil reservoir, the experiment methods including scanning electron microscope (SEM), rate-controlled mercury injection (RMI) and pressure-controlled mercury injection (PMI) were performed on the six sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The pore types and sizes can be qualitatively observed by CT scan [12], scanning electron microscope (SEM) [13], field emission scanning electron microscope (FESEM) [14], and transmission electron microscope (TEM) [15]. Meanwhile, quantitative characterization methods include high pressure mercury injection (PMI) [16], constant rate mercury injection (RMI) [17], nuclear magnetic resonance (NMR) [18,19], low-temperature N 2 and CO 2 adsorption [20,21], small-angle and ultra-small-angle neutron scattering (SANS and USANS) [22], etc. Each method has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The pore types and sizes can be qualitatively observed by CT scan [12], scanning electron microscope (SEM) [13], field emission scanning electron microscope (FESEM) [14], and transmission electron microscope (TEM) [15]. Meanwhile, quantitative characterization methods include high pressure mercury injection (PMI) [16], constant rate mercury injection (RMI) [17], nuclear magnetic resonance (NMR) [18,19], low-temperature N 2 and CO 2 adsorption [20,21], small-angle and ultra-small-angle neutron scattering (SANS and USANS) [22], etc. Each method has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The number of pores (radius > r) can be expressed by Equation ( 1) on the bas fractal principle [25]. When the pore radius is calculated, pores are regarded as ideal spheres, th formula in Equation ( 3) can be obtained after a series of mathematical transfor the detailed process was described in [26].…”
Section: Fractal Dimensions Calculated From Hmipmentioning
confidence: 99%
“…The smaller the pore aperture, the larger the fractal dimension, the more complex the pore structure, and the lower the permeability (Wang et al 2019a(Wang et al , 2020. Wang et al (2019b) reported that when the fractal dimension exceeded 2.586, a tight reservoir did not favor oil accumulation. If the fractal dimension was approximately 3, the porosity and permeability of the tight reservoir would decrease significantly (Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%